The mud-shrimp genus Axianassa Schmitt, 1924 (Crustacea, Decapoda, Axianassidae) in the Indo-West Pacific, with description of a new species from French Polynesia - Anker, Arthur (Zootaxa, 2010)
A new species of the mud-shrimp genus Axianassa Schmitt, 1924 is described based on four specimens collected in a muddy near-shore area inside the Moorea lagoon, Society Islands, French Polynesia. Axianassa ngochoae n. sp. constitutes the first Indo-West Pacific record of this genus, previously known only from the western and eastern coasts of the Americas. A key to all species of Axianassa is provided.